USING DISTANCE COMMUNICATION AND COLLABORATION TOOLS FOR GENERAL SOCIAL SERVICES - Gudzinskiene, Vida; Mačiuikienė, Diana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
This paper discusses the use of communication and collaboration tools in the delivery of social services, based on the results of a qualitative study. The research question is what kind of remote communication and collaboration tools are used by social workers in the provision of social services. The paper focuses on the use of telecommunication and collaboration tools by social workers in their service delivery and activities. The study involved 22 social workers employed in social institutions in different parts of Lithuania providing complex services to families.The study found that social workers use mobile devices and that the most convenient and acceptable means of remote communication and collaboration are learning environments, audio and video data storage (YouTube), conferencing and chat software (MS Teams, Zoom, Google Meet, Skype, Facebook Messenger, Viber, WhatsApp, Board Connect, Telegram), social networks (Facebook, Messenger), technical means (smart phone, computer, Internet connection).